О спектральных вопросах и разрешимости одного особого интегрального уравнения Вольтерра второго рода - Есбаев, А.Н.; Рамазанов, М.И. (Изд-во КарГУ, 2010)
Мақалада Меллин түрлендіру əдісімен Вольтеррдің екінші текті интегралдық теңдеуі зерттелген. Сəйкес келетін интегралдық операторының ядросына белгілі шарттар қойылған. Берілген теңдеудің шешілгіштік шарттарымен спектрі табыған. In the given article the integral equation of Volterra of second kind with the given conditions, some properties of kernel of this equation, the spectrum and also the solution of study equation with the application of integral transformation of Mellin have been investigated.
About spectrum questions and about the solvability of one singular integral equation of Volterra of the second kind